User-Centric Services Provisioning in Wireless Environments. - SHENG, QUAN Z.; BENATALLAH, BOUALEM; MAAMAR, ZAKARIA (Communications of the ACM, 2008)
The article discusses the seamless provisioning of data and services to users in sophisticated wireless communication infrastructures, examining issues surrounding personalized access to services as well as handling limited resources of mobile devices. Mobile applications will utilize ubiquitous wireless networking to create virtual worlds with which people will interact, the article states. Other topics include the requirement for integrated access to relevant services and mobile devices acting as passive listeners.